2014
DOI: 10.1089/pop.2013.0095
|View full text |Cite
|
Sign up to set email alerts
|

Worksite Primary Care Clinics: A Systematic Review

Abstract: Despite levels of health spending that are higher per capita and as share of gross domestic product than any country worldwide, the US health care system is fragmented, technology and administration heavy, and primary care deficient. Studies of regional variations in US health care show similar "disconnects" between higher spending and better health outcomes. Faced with rising health benefit costs and suboptimal workforce health amid economic downturn, concerned US employers have implemented innovative payment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Across the four jurisdictions, access to care was mainly conceptualized in terms of temporal access. These included articles discussing the timeliness of the first health care encounter, the delay before filing in the injury certification form, and issues and problems in accessing different types of HCPs in a timely fashion . For example, authors studying Ontario found that “42.3% of participants had their first health care consultation on the day of the injury, and 93.7% had their first consultation within the first week after the injury.” Having a more severe injury, consulting a physiotherapist as the first HCP or the fact that the employer had doubts about the work‐relatedness of the injury were factors that were associated with increased time to care .…”
Section: Resultsmentioning
confidence: 99%
“…Across the four jurisdictions, access to care was mainly conceptualized in terms of temporal access. These included articles discussing the timeliness of the first health care encounter, the delay before filing in the injury certification form, and issues and problems in accessing different types of HCPs in a timely fashion . For example, authors studying Ontario found that “42.3% of participants had their first health care consultation on the day of the injury, and 93.7% had their first consultation within the first week after the injury.” Having a more severe injury, consulting a physiotherapist as the first HCP or the fact that the employer had doubts about the work‐relatedness of the injury were factors that were associated with increased time to care .…”
Section: Resultsmentioning
confidence: 99%
“…4 However, fewer employers offered an approach that included primary care. 5,6 As of 2016, only 10% of employers with 200 or more workers and nearly a quarter of employers with 1000 or more workers offered medical services to employees on-site for improved access to care. 5…”
Section: Purposementioning
confidence: 99%
“…Employers' primary reasons for providing a worksite medical home to employees are to reduce absenteeism, reduce overall health care costs, and improve management of employee health risks and chronic conditions. 11,12 One way to reduce health care costs is to reduce emergency department (ED) visits and hospitalizations. One study concluded that 56% of visits to the ED by members of a group that had employer-provided health benefits could have been handled outside of the ED.…”
Section: Introductionmentioning
confidence: 99%
“…15 Due to the relative newness of the worksite medical home paradigm, data on its utilization and on health outcomes for employees who receive their primary care from one of these clinics are still limited. 12,16 A recent study found that employees who had access to a worksite clinic that provided episodic care had fewer ED visits than those who did not have access to such a clinic. 17 Although that study was limited to the evaluation of a clinic that offered only episodic or acute care, it suggests that any worksite clinic where employees can obtain primary care services could reduce the use of the ED.…”
Section: Introductionmentioning
confidence: 99%